Netflix: Implementasi Strategi Korporasi pada Strategi Fungsional SDM untuk Pencapaian Keunggulan Komparatif - Ade Maryam Derek; Chandra Liu; Putri Melati (Sanskara Manajemen Dan Bisnis, 2023)
This research aims to increase knowledge about information about Netflix's successful strategies and what are the competitive advantages for Netflix so that people use Netflix as a medium of entertainment. The research method used is literature study. The results of this study indicate that the strategy used by Netflix in achieving competitive advantage can be seen from Netflix's Vision, Mission and core values by using a SWOT analysis to look at internal and external factors that can affect the organization including internal strengths and weaknesses, while for external factors, namely Opportunities and Threats.